Interfaces between language and culture in medieval England : a festschrift for Matti Kilpiö - Hall, Alaric; Kilpiö, Matti (Northern world, 2010)
The twelve articles in this volume promote the growing contacts between medieval linguistics and medieval cultural studies generally. Articles address medieval English linguistics, and the interrelation in Anglo-Saxon England between Latin and vernacular language and culture.